The Relevance of Ingrid Mattson's Socio-Historical Critical Reasoning to Hadith Contextualization Approaches - Sulis Nuriyawati; Budi Ichwayudi; Maulidatus Syahrotin Naqqiyah (al-Afkar, Journal For Islamic Studies, 2025)
The study of Islamic Studies based on the normative laws of the Qur'an and hadith, theoretically its scientific ranks complement each other as the authority of bayan text with a bound level. Contextual interpretation in interpreting the text of the Qur'an and hadith, in addition to the demands of the times for the redaction of the text to be substantive, is also a value of critical reasoning knowledge of the text. Hadith interpretation within the scope of hadith science is part of the conceptual framework of the hermeneutic approach, through contextualization ijtihad. The significance of hermeneutics with contextualization substantially starts from the analysis of the historical context of hadith. Based on the background of the continuing development of hadith studies. This research formulates a main problem formulation, namely how the relevance of Ingrid Mattson's socio-historical criticism reasoning to the Hadith contextualization approach. The purpose of this study is to explore the reasoning of Mattson's socio-historical criticism that is able to interconnect the efforts of contextual ijtihad in hermeneutic theory as enriching the understanding of hadith for modern Muslim communities. The research method used is a qualitative method based on reference sources of books and journals (library research). The focus of the research is Mattson's reasoning of socio-historical criticism in criticizing the text has relevance in the approach of contextualization of hadith. The results of this study found that contextualization is part of the purpose of interpreting the text, so that the ijtihad reasoning of contextualization comes from the analysis of hermeneutic theory.